Linear dust polarization during the embedded phase of protostar formation: synthetic observations of bridge structures - Küffmeier, Michael; Reißl, Stefan; Wolf, Sebastian; Stephens, I.; Calcutt, Hannah (Astronomy and astrophysics, 2020)
Context. Measuring polarization from thermal dust emission can provide important constraints on the magnetic field structure around embedded protostars. However, interpreting the observations is challenging without models that consistently account for both the complexity of the turbulent protostellar birth environment and polarization mechanisms.Aims. We aim to provide a better understanding of dust polarization maps of embedded protostars with a focus on bridge-like structures such as the structure observed toward the protostellar multiple system IRAS 16293-2422 by comparing synthetic polarization maps of thermal reemission with recent observations.Methods. We analyzed the magnetic field morphology and properties associated with the formation of a protostellar multiple based on ideal magnetohydrodynamic 3D zoom-in simulations carried out with the RAMSES code. To compare the models with observations, we postprocessed a snapshot of a bridge-like structure that is associated with a forming triple star system with the radiative transfer code POLARIS and produced multiwavelength dust polarization maps.Results. The typical density in the most prominent bridge of our sample is about 10−16 g cm−3, and the magnetic field strength in the bridge is about 1 to 2 mG. Inside the bridge, the magnetic field structure has an elongated toroidal morphology, and the dust polarization maps trace the complex morphology. In contrast, the magnetic field strength associated with the launching of asymmetric bipolar outflows is significantly more magnetized (~100 mG). At λ = 1.3 mm, and the orientation of the grains in the bridge is very similar for the case accounting for radiative alignment torques (RATs) compared to perfect alignment with magnetic field lines. However, the polarization fraction in the bridge is three times smaller for the RAT scenario than when perfect alignment is assumed. At shorter wavelength (λ ≲ 200 μm), however, dust polarization does not trace the magnetic field because other effects such as self-scattering and dichroic extinction dominate the orientation of the polarization.Conclusions. Compared to the launching region of protostellar outflows, the magnetic field in bridge-like structures is weak. Synthetic dust polarization maps of ALMA Bands 6 and 7 (1.3 mm and 870 μm, respectively) can be used as a tracer of the complex morphology of elongated toroidal magnetic fields associated with bridges.
Gesehen am 28.09.2020